(untitled) (Journal of Hama University, 2020)
The aim of the current research is to identify the degree of use of smart phones in the educational process, and to identify the differences in the variables (gender, educational qualification, years of experience) on using smart phones in the educational process. The original community of the research consisted of (2207) teachers, and the research sample consisted of (341) male and female teacher, and the study followed the descriptive analytical method, adopted the questionnaire as a data collection tool, and used the statistical program (SPSS) to reach the results. The search results were: - There degree of use of smart phones in the educational process by teachers of the first cycle of basic education was low, average (1.92) and standard deviation (1.31). - There were no statistically significant differences between the averages of male and female teachers ’grades for the first cycle of basic education to the degree of using smart phones in the educational process due to the variable (gender). - There were no statistically significant differences between the averages of male and female teachers ’grades for the first cycle of basic education to the degree of using smart phones in the educational process due to the variable ( educational qualification). - There were no statistically significant differences between the averages of male and female teachers ’grades for the first cycle of basic education to the degree of using smart phones in the educational process due to the variable (years of experience).